Decision support system for selecting tourist attractions using fuzzy analytic hierarchy process - Christa Bire; Daniel Kasse; Rio Bire (Institute of Advanced Engineering and Science, 2021)
The selection of tourist attractions is a multi-criteria decision making problem, which requires time and careful consideration to make the right decision. The proper destination selection based on human needs in a particular moment affects satisfaction in traveling. This research aims to create a decision support system for selecting tourist attractions (a case study in Kupang City) using fuzzy analytic hierarchy process method. Users can input the priority scale of 9 human need attributes and then be directed to the system’s recommendations of tourist attractions. This paper also compares fuzzy analytic hierarchy process method with the original analytic hierarchy process calculations. The result shows that both methods can be a solution for multi-criteria decision making, but the fuzzy analytic hierarchy process method performs a more optimal solution for cases with uncertainty in comparisons between elements.